Experimental Study on the Riverbed Coarsening Process and Changes in the Flow Structure and Resistance in the Gravel Riverbed Downstream of Dams - Zhou, Yinjun; Lu, Jinyou; Jin, Zhongwu; Li, Yuan; Gao, Yu; Liu, Yujiao; Chen, Peng (Frontiers in Environmental Science, 2021)
After the completion of a dam, sediment is intercepted and sediment concentration of the discharged flow is greatly reduced. This causes riverbed scouring and flow structure adjustment in the downstream reach and affects the river habitat. Based on the generalized flume test with different bed sand composition and different discharge, the scouring adjustment process of the channel composed of sand pebble riverbed downstream of the dam is simulated. The results show that the composition of bed sediment affects the water surface gradient, scour depth, turbulence intensity, and sand resistance directly after final scouring. The bed sediment with coarser grains has the largest final turbulence intensity and sand resistance, while the bed sediment with less coarse grains has greater scouring degree and the comprehensive resistance with moderate coarse grains has the largest change. While coarsening, the sand resistance is exponentially and positively correlated with the median grain size and the fractal dimension of bed sediment mass. A formula for calculating the sand resistance coefficient, by using the mass fractal dimension, Froude number, and median particle size is proposed. In addition, the relationship between it and the adjusted grain resistance was established, which will be of great help in calculating resistance changes in the sandy gravel-bed river reaches downstream of the dam and predicting their effects on the aquatic habitat.